Mitochondrial-related effects of pentabromophenol, tetrabromobisphenol A, and triphenyl phosphate on murine BV-2 microglia cells. (September 2020) - Bowen, Christine; Childers, Gabrielle; Perry, Caroline; Martin, Negin; McPherson, Christopher A.; Lauten, Tatlock; Santos, Janine; Harry, G. Jean
Abstract: The predominant reliance on bromated flame retardants (BFRs) is diminishing with expanded use of alternative organophosphate flame retardants. However, exposure related issues for susceptible populations, the developing, infirmed, or aged, remain given environmental persistence and home-environment detection. In this regard, reports of flame retardant (FR)-related effects on the innate immune system suggest process by which a spectrum of adverse health effects could manifest across the life-span. As representative of the nervous system innate immune system, the current study examined changes in microglia following exposure to representative FRs, pentabromophenol (PBP), tetrabromobisphenol A (2, 2′, 6, 6′, -tetrabromo-4, 4′-isopropylidine diphenol; TBBPA) and triphenyl phosphate (TPP). Following 18hr exposure of murine BV-2 cells, at dose levels resulting in ≥80% viability (10 and 40 μM), limited alterations in pro-inflammatory responses were observed however, changes were observed in mitochondrial respiration. Basal respiration was altered by PBP; ATP-linked respiration by PBP and TBBPA, and maximum respiration by all three FRs. Basal glycolytic rate was altered by PBP and TBBPA and compensatory glycolysis by all three. Phagocytosis was decreased for PBP and TBBPA. NLRP3 inflammasome activation was assessed using BV-2-ASC (apoptosis-associated speck-like protein containing a CARD) reporter cells to visualize aggregate formation. PBP, showed a direct stimulation of aggregate formation and properties as a NLRP3 inflammasome secondary trigger. TBBPA showed indications of possible secondary triggering activity while no changes were seen with TPP. Thus, the data suggests an effect of all three FRs on mitochondria metabolism yet, different functional outcomes including, phagocytic capability and NLRP3 inflammasome activation. Highlights: PBP, TBBPA, or TPP exposure modified mitochondrial bioenergetics of microglia. PBP and TBBPA showed potential as trigger for NLRP3 inflammasome activatio. PBP and TBBPA diminished phagocytic capability. FR exposure did not inhibit response to LPS.